Note on two genera proposed by Gistel in 1834 - Bousquet, Yves (Zootaxa, 2018)
The genera Geocharis and Caloclyptus, proposed by Gistel in 1834, are placed in synonymy with Molops Bonelli, 1810 (n. syn.). Geocharis thoracica and Caloclyptus jenisonii, also described by Gistel in 1834, are nomina dubia but, for pratical reasons, are placed in synonymy with Molops striolatus Fabricius, 1801 (n.syn.). Geocharis Gistel, 1834 is declared nomen oblitum and Geocharis Ehlers, 1883 nomen protectum.